EP1219 Added value of para-aortic surgical staging compared to F18 FDG PET/CT on the external beam radiation field of patients with locally advanced cervical cancer: an ONCO-GF study. (1st November 2019) - De Cuypere, M; Lovinfosse, P; Goffin, F; Schoenen, S; Rovira, R; Duch, J; Fastrez, M; Gebhart, G; Luyckx, M; Squifflet, J-L; Charaf, G; Crener, K; et al.
Abstract : Introduction/Background: Extended field chemoradiation is recommended for patients with locally advanced cervical cancer (LACC) and para-aortic lymph node (PALN) metastases. The radiation planning may be based on the positron emission tomography-computed tomography (PET/CT) while others recommend to rely on a surgical staging. We report the rate of patients for whom the radiation field defined on a PET/CT basis was modified by the histological PALN status. Methodology: Between March 2010 and December 2016, 168 consecutive patients with LACC underwent a pre-therapeutic PET/CT and PALN dissection. The data were reviewed retrospectively. The diagnostic performance of the PET/CT for definition of PALN status was calculated. We determined the percentage of patients for whom PALN dissection altered the external beam radiation treatment (EBRT) field defined on the PET/CT basis. Results: Of the 151 patients with negative PALNs on PET/CT, 26 had histological PALN metastasis. Of the 17 patients with positive PALNs on PET/CT, 9 were negative on histology. Seven of these 9 false positive cases were located in the common iliac region. Sensitivity, specificity, positive and negative predictive value of PET/CT were 23.5, 93.3, 47.1 and 82.8% respectively. In total, 35 out of 168 patients underwent EBRT-field adaptation (pelvic vs extended field). The rate of radiation field modification was particularly high (27, 7%) in the subgroup of patients with metastatic pelvic lymph nodes (PLNs) on PET/CT. Conclusion: Para-aortic surgical staging contributes significantly to individualize the radiation treatment of patients with LACC, particularly for those with positive PLN at PET/CT. Indication of surgical staging deserves particular attention when the PET/CT suggests positive lymph nodes in the common iliac region. Disclosure: Nothing to disclose.